CARA IDENTIFIKASI PENGETAHUAN PROSEDURAL DAN PEMAHAMAN KONSEPTUAL MAHASISWA TERHADAP MATERI LIMIT - Mulyono, Budi; Kusumah, Yaya S; Rosjanuardi, Rizky (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
Limit is the main topic in calculus which is already introduced and thought to students since senior high school level. However, quite a lot of students find difficult to learn and to understand limit at the first year of university level. This article discusses how to identify student’s procedural-knowledge and conceptual- understanding about limit. The method used to identify student’s procedural-knowledge and conceptual- understanding about limit was by giving a test to students about limit problems. The problems were designed so simple in order to avoid mistakes that students made because of the difficulty of questions. The finding of test results show that there were some students whom could answer questions about limit procedurally well, but they had problem to solve questions about limit related to conceptual understanding. This problem could be caused by the learning about limit when they were at senior high school level only focused on how to solve questions about limit procedural.DOI: 10.22342/jpm.13.1.6706.73-82